Determinant factors in maintenance practice implementation in relation to conservation principles towards good conservation practice in Malaysia / Amir Fasha Mohd Isa - Mohd Isa, Amir Fasha (2023)
Recent phenomenon witnesses conserved heritage building acceptance as an important national policy in Malaysia. Essentially in 2008 Melaka and Georgetown the historical cities were enrolled as UNESCO's World Heritage Site. However, being internationally recognized World Heritage Site come with international accountability. This study comprised critical review of existing literature and highlighting some fundamental principles in conservation of historic building and it influence to the maintenance practice. This research aims to develop a model of effective maintenance practice in relation to conservation principles for heritage buildings in Malaysia. Three objectives were set for the study. The first is to identify the maintenance practice criteria in relation to conservation principles based on international conservation charters and guidelines. The second research objective is to examine the critical factor of maintenance practice in relation to conservation principles by the maintenance practitioner of heritage buildings in Malaysia. Finally, the third objective is to propose a model of effective maintenance practice in relation to conservation principles for heritage buildings in Malaysia. This study employed the philosophy of positivism with a deductive approach and survey strategies. The conceptual framework is developed based on the international conservation charters and guidelines and an extensive review of the existing literature. The main data collection method is through a questionnaire distributed during the survey. The data were collected from the maintenance practitioner of the conserved heritage building in peninsular Malaysia. Among the population were registered conservator with Jabatan Warisan Negara, professional such as architect, building surveyor, curator and contractor which in total 110 population. From which 60 respondents have replied giving the exceeding minimum sample size. The data were initially analysed using Statistical Package for Social Science (SPSS 21) for factor analysis to achieve second and third objective. The reliability test of Cronbach's Alpha shows that nine determinant factors group for MP and CP has good reliability for each answer itemized in the questionnaire survey. As of the analysis, the results show that all determinant factors for MP in relation to CP has high level of reliability which is 0.908 that exceed the threshold value of 0.70. Next, further analysis using factor analysis was conducted to assess the loading for each item. It involved three stages which are preliminary analysis, factors extraction and factors rotation. There are eight groups of determinant factors have been identified with only twenty-eight attributes. The model concludes that the conservation principles have a significant relationship between maintenance practice implementation. The findings of this study indicated that good conservation practice can be achieve through maintenance practice implementation in relation to conservation principles. As an implication, this final model could potentially be a guide for policymakers, practitioners and scholars. It assists in improving built heritage maintenance performance at large. These findings have contributed to filling the knowledge gap by explaining the maintenance practice is one of the important perspectives that still leave a gap in effective management strategies. This research finally aims to establish Malaysian conserved heritage building best maintenance practice guidelines.